Analysis of Multiball and Pair Training on The Forehand Drive Accuracy of Table Tennis Athletes of The Anjam Slawi Club - Azhar Mufatihul Huda; Moch. Fahmi Abdulaziz (Universitas Negeri Semarang, 2026)
The purpose of this study was to determine which training had a greater effect on the accuracy of forehand drive shots in Anjam Slawi Club athletes, whether multiball training or pair training. The type of research used was an experimental study with a pretest-posttest design. The research population was 10 Anjam Slawi Club athletes, with a sample of 10 athletes using a saturated sampling method. This study was divided into 2 groups, multiball and pair training, each group consisting of 5 athletes. Multiball training was measured with 50 balls for 5 minutes, where the subject hit the ball using a forehand drive towards the target, and the score was determined based on the number of balls that entered the target. Pair training was carried out by hitting with an opponent like a match for 5 minutes. The Wilcoxon test showed that multiball training 0.43 and pair training 0.43 had a significant effect (p <0.05). In the T test, the mean value of the multiball pretest was 147.40 and the multiball posttest was 175.80 with a difference of 28. As well as the mean value of the paired training pretest was 141.00 and the paired posttest was 163.60 with a difference of 22. If seen from the difference in the mean value of multiball and paired training, it can be concluded that multiball training has a greater influence on improving forehand drive strokes in Anjam Slawi Club athletes. Thus, this study suggests using the multiball training method.